Thermoelectric properties of the layered oxides LnBaCu(Co)FeO₅₊δ(Ln = La, Nd, Sm, Gd) - Klyndyuk, A.I.; Chizhova, Ye.A. (Functional Materials, 2009)
The crystal structure, electrical conductivity and thermo-e.m.f. of layered oxides LnBaCu(Co)FeO₅₊δ(Ln=La, Nd, Sm, Gd) of perovskite structure have been studied. The LnBaCu(Co)FeO₅₊δ compounds have cubic structure for Ln = La and tetragonal one for the Ln = Nd-Gd and are p-type semiconductors (except for LaBaCoFeO₅₊δ having negative S values). The activation energy of electric transport, thermoelectric coefficients (Seebeck, Pel tier and Thomson) and the power factor of the oxides studied have been determined. The power factor of LnBaCu(Co)FeO₅₊δ phases has been found to depend on the nature of rare earth elements and 3d-metals in their structure and to be maximum for SmBaCuFeO₅₊δ, GdBaCuFeO₅₊δ and NdBaCoFeO₅₊δ. The layered perovskites can be considered as a base for development of the new thermoelectric oxide materials. Досліджено кристалічну структуру, електропровідність та термо-ЕРС шаруватих оксидів LnBaCu(Co)FeO₅₊δ(Ln=La, Nd, Sm, Gd) зі структурою перовскіту. Сполуки LnBaCu(Co)FeO₅₊δ мають кубічну структуру для Ln = La та тетрагональну - для Ln = Nd-Gd та є напівпровідниками р-типу (окрім LaBaCoFeO₅₊δ, для якого S < 0). Визначено значення знергії активації процесів електроперенесення, обчислено величини термоелектричних коефіцієнтів (3еебека, Пельтьє та Томсона) і фактора потужності досліджених оксидів. Виявлено, що значення фактора потужності фаз LnBaCu(Co)FeO₅₊δ залежать від природи рідкісноземельних елементів та 3d-металів, які входять до їх складу, і є максимальними для SmBaCuFeO₅₊δ, GdBaCuFeO₅₊δ та NdBaCoFeO₅₊δ. Показано, що шаруваті перовскіти можна розглядати як основу для розробки нових оксидних термоелектричних матеріалів. Исследованы кристаллическая структура, электропроводность и термо-ЭДС слоистых оксидов LnBaCu(Co)FeO₅₊δ(Ln=La, Nd, Sm, Gd) со структурой перовскита. Соединения LnBaCu(Co)FeO₅₊δ имеют кубическую структуру для Ln = La и тетрагональную - для Ln = Nd-Gd и являются полупроводниками р-типа (кроме LaBaCoFeO₅₊δ, для которого S < 0). Определены значения энергии активации процессов электропереноса, термоэлектрических коэффициентов (3еебека, Пельтье и Томсона) и фактора мощности изученных оксидов. Найдено, что значения фактора мощности фаз LnBaCu(Co)FeO₅₊δ зависят от природы входящих в их состав редкоземельных элементов и 3d-металлов и максимальны для SmBaCuFeO₅₊δ, GdBaCuFeO₅₊δ и NdBaCoFeO₅₊δ. Показано, что слоистые перовскиты можно рассматривать как основу для разработки новых оксидных термоэлектрических материалов.